Energy harvesting from longitudinal and transverse motions of sea waves particles using a new waterproof piezoelectric waves energy harvester. (December 2021) - Kazemi, Shahriar; Nili-Ahmadabadi, Mahdi; Tavakoli, Mohammad Reza; Tikani, Reza
Abstract: This paper experimentally studied the energy harvesting from the longitudinal and transverse motions of sea waves using a waterproof piezoelectric wave energy harvester (WPWEH). Because of sealing and specific design type of the WPWEH, the piezoelectric cantilever beam was entirely placed inside the water to increase the harvested electrical power. Three orientations of O 1, O 2 and O 3 were considered for placing the piezoelectric cantilever beam inside the water channel. In O 1 orientation, the cantilever beam was vertical and perpendicular to the floor while in O 2 and O 3 orientations, it was horizontal and parallel with the floor. The cantilever beam was perpendicular to the flow in O 1 and O 2 and vibrates due to the longitudinal motion of wave particles while it was parallel with the flow in O 3 and vibrates due to the transverse motion of wave particles. The influence of orientation, wave rate, and resonant frequency of the cantilever beam on the root mean square of the voltage and harvested electrical power was studied. The O 1 orientation was selected as the optimum orientation for energy harvesting, because of having harmonic oscillations with a maximum generated voltage. The optimum electrical load resistance was calculated for the maximum harvested power. The results showed that the maximum density of the harvested electrical power from the WPWEH was increased compared to the other similar works. Highlights: A waterproof piezoelectric wave energy harvester was designed. Energy was harvested from the longitudinal and transverse motions of the sea waves. A special sealing of epoxy resin and rubber coating was used. The electrical power efficiency of the system increased by the special sealing. A practical model was suggested to supply the power of measurement sensors.